The Challenge Of Character Education In The Midst Of The Tension Between Educational Idealism And Social Reality - Febriona Maharani Ariqah; Widiya Yul (LPPM Institut Pendidikan Nusantara Global, 2026)
Character education is a fundamental aspect of the educational process, aiming to shape students who are not only intellectually superior but also possess moral, social, and spiritual integrity. However, in practice, character education faces various challenges stemming from the tension between educational idealism and evolving social realities. This article aims to critically examine the challenges of character education amidst contemporary social dynamics through a literature review approach. Fifteen national and international journal articles were analyzed using content analysis methods to identify patterns, findings, and key issues related to the implementation of character education. The study results indicate that character education still tends to be normative and institutional, while the social realities of students, influenced by their family environment, community, and digital media, often align with the values taught in schools. This tension leads to value dissonance and weakens the process of character internalization. This article emphasizes that character education needs to be understood as a social process that is dialectical, contextual, and adaptive to social change, so as not to become trapped in normative idealism that is difficult to realize in educational practice